Control Structure On Damage Zone and Fault Plane to Geometry Of Quartz Veins and Calcite In Muaradua Ogan Komering Ulu Selatan, South Sumatra, Indonesia - Budhi Setiawan; Pratama Goestyananda (UIR PRESS, 2022)
Geological mapping was carried out on the Gilas and Malau rivers in the Muaradua area, South Ogan Komering Ulu Regency, South Sumatra by observing the presence of joints, faults, and veins in the granite and phyllite rock outcrops of the Tarap Formation. Research on pattern geometry and vein type in the crushing zone is focused on measuring the direction (trend) of veins and joints. The measurement results are then analyzed to obtain a general pattern of quartz and calcite veins so that the orientation of their development can be known. The method used in this study is in the form of determining the orientation and geometry of the veins based on classifications that refer to several studies, then an analysis is carried out using DemNAS data to determine the general direction of the straightness pattern of the study area. The quartz veins that developed in the study area have an extensional fracture type with the geometry found in the form of isolated, abutting, cutting, mutually-cutting, and crosscutting. The veins that develop in the research area are relatively north-south and west-east and indicated the presence of a fault and traces of deformation that occurred in the study area. With the help of veins and joints found in the study area, it is possible to determine the structural control of the presence of a crushing zone in the fault plane.